2016
DOI: 10.1017/s0033291716000167
|View full text |Cite
|
Sign up to set email alerts
|

TheCHRM3gene is implicated in abnormal thalamo-orbital frontal cortex functional connectivity in first-episode treatment-naive patients with schizophrenia

Abstract: Overall, we identified the first evidence that the CHRM3 gene plays a role in abnormal thalamo-orbital frontal cortex functional connectivity in first-episode treatment-naive patients with schizophrenia. Identification of these genetic variants using neuroimaging genetics provides insights into the causes of variability in human brain development, and may help us determine the mechanisms of dysfunction in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Furthermore, it was assumed that the effect of genetics on functional networks between healthy people and their siblings was insignificant. Some recent studies have found an effect of genetics on functional networks between schizophrenia and their sibling [50]. Third, every schizophrenic subject was taking antipsychotic medication at the time of the diagnostic test.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was assumed that the effect of genetics on functional networks between healthy people and their siblings was insignificant. Some recent studies have found an effect of genetics on functional networks between schizophrenia and their sibling [50]. Third, every schizophrenic subject was taking antipsychotic medication at the time of the diagnostic test.…”
Section: Discussionmentioning
confidence: 99%
“…As for the CHRM3 gene, which is a cholinergic receptor and is related to schizophrenia, it may be a potential therapeutic target for COPD patients (30,31). And we found six antipsychotic drugs targeting CHRM3.…”
Section: Discussionmentioning
confidence: 86%
“…The genotype data has been used by our previous studies and the details of genotyping and quality control have been published elsewhere 14 , 15 . In brief, DNA extracted from whole blood sample was genotyped using HumanOmniZhongHua-8 BeadChip (Illumina, San Diego, CA) and the raw genotype data underwent systematic quality control steps (QCs) including missing rate per genotype (< 5%) and per individuals (< 3%), minor allele frequency (MAF, < 0.01), Hardy-Weinberg equilibrium tests ( p < 0.001), cryptic relatedness and heterozygosity rate.…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al . later used functional connectivity as the QTs in GWAS of schizophrenia and found that the CHRM3 gene was significantly associated with functional connectivity deficits in schizophrenia 15 . These studies highlighted the efficacy of QTs as the endophenotype in exploring the pathogenesis of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%